2018
DOI: 10.1007/s00436-018-5908-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of selected zoonotic food-borne parasites and first molecular identification of Alaria alata in wild boars (Sus scrofa) in Italy

Abstract: Wild boar is a source of human infections with zoonotic pathogens, including food-borne parasites. With the aim of a characterization of the human exposure risk, a survey on wild boars intended for human consumption was planned, selecting three pathogens, Toxoplasma gondii, Alaria alata, and Trichinella spp., as markers of meat infection. Diaphragm muscle samples from 100 wild boars hunted in Piedmont region (Northern Italy) in two hunting seasons (2015-2016) were collected. Concerning T. gondii, a combined ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 65 publications
5
33
2
Order By: Relevance
“…The presented study confirmed a high prevalence of T. gondii antibodies in the investigated animals (48%, n=50), which makes Poland one of the countries with the highest percentage of T. gondii seropositive wild boar. Similar results were obtained in Spain (38.4%, MAT) [48], Italy (43.3%, ELISA) [32], Sweden (49.5%, ELISA) [49], and the Czech Republic (39.6%, ELISA) [9]. The percentage of seropositive wild boar was lower in several studies conducted in the Czech Republic (15.4% and 26.2%) [31,37], Spain (23.8%) [50] and Sweden (28.6%) [29], as well as in France (16.8% and 17.6%) [4,51], Switzerland (6.7%) [2], The Netherlands (24.4%) [39], Slovakia (8.1%) [3], Finland (33%) [52], Portugal (20.6%) [1], Denmark (27.7%) [53], Greece (5.2%) [25], Romania (16%) [54], Italy (14%) [55], Latvia (33.2%) [56] and Estonia (24%) [38].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The presented study confirmed a high prevalence of T. gondii antibodies in the investigated animals (48%, n=50), which makes Poland one of the countries with the highest percentage of T. gondii seropositive wild boar. Similar results were obtained in Spain (38.4%, MAT) [48], Italy (43.3%, ELISA) [32], Sweden (49.5%, ELISA) [49], and the Czech Republic (39.6%, ELISA) [9]. The percentage of seropositive wild boar was lower in several studies conducted in the Czech Republic (15.4% and 26.2%) [31,37], Spain (23.8%) [50] and Sweden (28.6%) [29], as well as in France (16.8% and 17.6%) [4,51], Switzerland (6.7%) [2], The Netherlands (24.4%) [39], Slovakia (8.1%) [3], Finland (33%) [52], Portugal (20.6%) [1], Denmark (27.7%) [53], Greece (5.2%) [25], Romania (16%) [54], Italy (14%) [55], Latvia (33.2%) [56] and Estonia (24%) [38].…”
Section: Discussionsupporting
confidence: 86%
“…The increase in their population size observed in recent years increases the risk of wild boar contact with people and pigs, and thus the risk of pathogen transmission, including zoonotic pathogens such as T. gondii [30]. The consumption of raw or undercooked meat is considered an important route of infection for humans [1,31,32,33,34]. However, the source of infection is difficult to determine [35], and varies depending on the populations tested (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present survey, aimed at estimating the presence of T. gondii in small ruminants' meats consumed in Italy, revealed seroprevalence values lower than those previously reported in sheep J o u r n a l P r e -p r o o f Journal Pre-proof (59.3%) and goats (41.7%) bred in Northern Italy [6]. In the study area, T. gondii showed to be widely spread also in other domestic [11,12] and wild animals [13][14][15]. Moreover, compared to the previous epidemiological survey [6] mostly focusing on adult meat producing sheep and dairy goats, in the present study both adult and young sheep and goats were sampled since a large proportion of lambs and kids are slaughtered in Italy (respectively 90.3% and 86%) (data obtained from the National Institute of Statistic, ISTAT, http://dati-censimentoagricoltura.istat.it/).…”
mentioning
confidence: 74%
“…Some parasites settle in the muscle tissue of hosts, e.g., Alaria spp., Trichinella spp., Spirometra sp., and Toxoplasma spp. ; thus, they can be ingested by humans eating raw or inadequately cooked meat (Dmitric et al 2018;Gazzonis et al 2018;Kołodziej-Sobocińska et al 2016c). It is important to carry out parasitological monitoring of wild animals, especially those that are hunted or live near human settlements, and therefore have the potential to become a threat to humans.…”
Section: Zoonosesmentioning
confidence: 99%